Legal Protection Of Customers Personal Data In Bank Financial Institutions - Astanti, Dhian Indah; Nuswanto, Heru -; Sukimin, Sukimin - (Faculty of Law, Universitas Pekalongan, 2024)
Since the legal connection between consumers and banks is one built on trust, legal protection for customers is crucial given that banks are financial entities whose operation cannot be divorced from the role of customers. Every individual has personal data, which is something that is intrinsic to them and has to be secured since everyone has the right to privacy, which is guaranteed by the Republic of Indonesia's 1945 Constitution and is a fundamental citizen right. The goal of this study is to identify the legal safeguards for the confidentiality of consumer information held by Bank Financial Institutions, as well as the legal actions that consumers may take in the event that their privacy is violated. This study employs a normative juridical research design, combining an analytical, historical, and legislative approach. The data type for the research specifications is secondary data, obtained through document/library research (Library Research), and the research standards call for analytical descriptive data. The research's data is organized logically and methodically, examined using qualitative analytic techniques, and then presented in a qualitative report. The study's findings indicate that state people have a constitutional right to privacy, which is the cornerstone of the legal protection of personal data. Both government control and self-regulation can be used to legally secure the personal data of customers. As of now, personal data is not legally based in any of Indonesia's laws or regulations. As a result, Indonesia lacks standards for the legal protection of personal data, making it unable to provide its residents with the best possible protection.